The Influence of Payment Methods, Discounts, and Free Shipping on Purchase Decisions in the Shopee Application for Generation Z in Surabaya City - Arde Agung Hidayatulloh; Ugy Soebiantoro (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
In shopping, purchasing decisions are influenced by consumer behavior, which is affected by several factors. One of the factors influencing purchase decisions is customer service. The Shopee application offers various customer services such as diverse payment methods, and monthly events like discounts or free shipping. Aligned with the services provided by Shopee, this study aims to determine the influence of payment methods, discounts, and free shipping on purchasing decisions among Generation Z in Surabaya City. The population studied consists of Generation Z in Surabaya City, and a purposive sampling technique was employed to select 100 respondents. Data collection was conducted using a questionnaire. Subsequently, the collected responses were analyzed to test the initial hypotheses using the Partial Least Squares (PLS) method, involving stages of validity testing, reliability testing, T-testing, and hypothesis testing. From the data analysis using the Partial Least Squares (PLS) method, it was found that payment methods, discounts, and free shipping significantly influence purchasing decisions. The impact of each independent variable indicates contributions of payment methods, discounts, and free shipping towards purchasing decisions on the Shopee application for Generation Z in Surabaya City.